A randomized clinical trial to compare levonorgestrel-releasing intrauterine system (Mirena) vs trans-cervical endometrial resection for treatment of menorrhagia - Ghazizadeh S; Bakhtiari F; Rahmanpour H; Davari-Tanha F; Ramezanzadeh F (Dove Medical Press, 2011)
Shirin Ghazizadeh1, Fatemeh Bakhtiari1, Haleh Rahmanpour2, Fatemeh Davari-Tanha1, Fatemeh Ramezanzadeh11Valie-Asr Reproductive Health Research Center, Valie-Asr Hospital, Tehran University of Medical Sciences, Tehran, Iran; 2Department of Obstetrics and Gynecology, Ayatollah Mousavi Hospital, Zanjan, IranObjective: To compare the acceptability, efficacy, adverse effects, and user satisfaction of the levonorgestrel intrauterine system (LNG-IUS) and trans-cervical resection of the endometrium (TCRE) for the treatment of menorrhagia.Method: 104 women with menorrhagia were divided into 2 groups: 52 women had the LNG-IUS inserted and 52 underwent TCRE. Menstrual pattern, pictorial blood loss assessment chart score, adverse effects, and rates of acceptability and satisfaction, were recorded at 6 and 12 months after the procedure.Results: After a year there were reductions of 93.9% and 88.4% in menstrual blood loss in the TCRE and LNG-IUS groups, respectively. Amenorrhea was more common in the TCRE group and spotting and systemic effects in the LNG-IUS group. Satisfaction rates of the TCRE group were higher than the LNG-IUS group (80.8% vs 69.2%), but the difference was not statistically significant.Conclusion: Although both treatments were found to be equally effective, LNG-IUS was less invasive and can be advised for younger women with a desire to preserve fertility.Keywords: menorrhagia, trans-cervical endometrial resection, levonorgestrel-releasing intrauterine system